Practicum Workshop and Learning Media Quality in the Light Vehicle Engineering Department of Vocational High Schools - Arief Kurniawan; Tri Kuat; Purnawan Purnawan (Universitas Ahmad Dahlan, 2020)
The study is to determine the quality of workshop practice and media learning of light vehicle engineering in Vocational High Schools in terms of (1) the facilities and infrastructure of laboratory and (2) the use of instructional media practices of light vehicle engineering. The collection of data used the method of observation, documentation, interview. This type of qualitative research is a case study approach, involving five internship supervisor teachers and workshop managers. The results of the study showed that the practice of Automotive Engine Repair with spacious 84 m2, Automotive Chassis Repair with a spacious 72 m2, Automotive Electrical Repair with spacious 24 m2 had not yet met the standard minimum as suggested at the Minister of Education and Culture Regulation number 34 of 2018. The use of practical learning media was less effective because: (1) the comparison of study groups with the area of the workshop was not balanced, (2) the existence of some practicum subjects scheduled in the same day resulted in the students were practicing simultaneously at one time, and (3) the lack of practicum facilities.